Review of Second-Generation Bioethanol Production from Residual Biomass - Robak, Katarzyna; Balcerek, Maria (Food technology and biotechnology, 2018)
In the context of climate change and the depletion of fossil fuels, there is a great need for alternatives to petroleum in the transport sector. This review provides an overview of the production of second generation bioethanol, which is distinguished from the first generation and subsequent generations of biofuels by its use of lignocellulosic biomass as raw material. The structural components of the lignocellulosic biomass such as cellulose, hemicellulose and lignin, are presented along with technological unit steps including pretreatment, enzymatic hydrolysis, fermentation, distillation and dehydration. The purpose of the pretreatment step is to increase the surface area of carbohydrate available for enzymatic saccharification, while minimizing the content of inhibitors. Performing the enzymatic hydrolysis releases fermentable sugars, which are converted by microbial catalysts into ethanol. The hydrolysates obtained after the pretreatment and enzymatic hydrolysis contain a wide spectrum of sugars, predominantly glucose and xylose. Genetically engineered microorganisms are therefore needed to carry out co-fermentation. The excess of harmful inhibitors in the hydrolysate, such as weak organic acids, furan derivatives and phenol components, can be removed by detoxification before fermentation. Effective saccharification further requires using exogenous hemicellulases and cellulolytic enzymes. Conventional species of distiller's yeast are unable to ferment pentoses into ethanol, and only a very few natural microorganisms, including yeast species like , ( ) and , metabolize xylose to ethanol. Enzymatic hydrolysis and fermentation can be performed in a number of ways: by separate saccharification and fermentation, simultaneous saccharification and fermentation or consolidated bioprocessing. Pentose-fermenting microorganisms can be obtained through genetic engineering, by introducing xylose-encoding genes into metabolism of a selected microorganism to optimize its use of xylose accumulated in the hydrolysate.